Lifestyle, Eating Habits, and Health Behaviors Among Dietary Supplement Users in Three European Countries - Iłowiecka, Katarzyna; Maślej, Monika; Czajka, Magdalena; Pawłowski, Adrian; Więckowski, Piotr; Styk, Tomasz; Gołkiewicz, Michał; Kuzdraliński, Adam; Koch, Wojciech (Frontiers in Public Health, 2022)
Dietary supplements (DS) are used by about 30–50% of adults in developed countries. However, only a few studies have compared the characteristics of DS users in different nations. This study aimed to identify and compare selected health-related behaviors of DS users from three European countries. A total of 3588 adults (32.08 ± 8.04 years) from Poland (1030 females, 287 males), Germany (994 females, 190 males), and the United Kingdom (911 females, 176 males) were included in the analysis. The study was based on a self-administered survey consisting of 70 questions regarding baseline characteristics, lifestyle, eating, and health habits. The associations of the obtained results were compared using the Kruskal–Wallis test, Pearson Chi-Square test, and Cramer’s V value. The highest percentage of DS users (56.98%, n=2044) had a correct body weight, while higher body weight values were observed in 39.19% (n=1406). In terms of lifestyle, statistically significant differences (p<0.005) were noted for alcohol consumption and the level of physical activity. Fruit and vegetables were most often consumed a few times a week (34.67%, n=1244). A similar result was observed for the consumption of whole grain (37.76%, n=1355), dairy (39.99%, n=1435), eggs (49.67%, n=1782), and meat (51.45%, n=1846). Most DS users did not have a chronic disease (66.72%, n=2394). Among the other conditions, a frequent occurrence (a few times a week) of gastrointestinal problems (28.29%, n=1015) and concentration disorders (29.15%, n=1046) was noted. Cramer’s V values (<0.3) indicated a weak (but significant p<0.05) relationship between the country of residence and most of the analyzed variables. In conclusion, DS users were characterized by a healthy lifestyle with appropriate behaviors but not healthy eating habits.